Online Business Training To Teenagers "Shelter Rumah Hati " For Ex-Prisoners - Tri Prasasti, Pinkan Amita (International Journal of Community Service Learning, 2018)
Community service team of Teachers Elementary School Education of PGRI University Madiun has conducted Online Business Training to Children and Youth Shelter Rumah Hati in Jombang. Shelter Rumah Hati is a place for ex-narapida children who have just come out of prisons and given mentoring there. The purpose of community service is: 1) To give knowledge about how to do business online to former inmates in Jombang House of the Heart, so they can open the job for themselves or others. 2) To provide assistance to children and adolescents who are in Shelter Rumah Hati Jombang. 3) To provide online-based skills to children and adolescents at Jombang Home Shelter. This training activity begins by meeting the shelter to seek permission to conduct online business training activities. We further deliver general material submissions on online business using lecture methods. After the delivery of materials, conducted activities of business practices online. After practice the way of our online business do mentoring process. The results of the training show that children and adolescents who are in Shelter Rumah Hati have a very high interest in online business, this can be seen from the questionnaire that we distributed to the children and adolescents there, they fill the satisfaction questionnaire with the value of the conversion of 87.8 means very good. Evaluation results related to the effectiveness of training also increased based on the N-Hake criteria with a value of 0.74 which means very good. Online Business Training at Jombang House Shelter in children and teenagers can be summed up that are interested and have the potential to open an online business